Associations between sleep duration, physical activity, and cognitive impairment in older adults—empirical analysis based on CHARLS data - Ma, Miao; Dong, Feng-Wei; Lan, Jin-Yan (Frontiers in Public Health, 2025)
ObjectiveTo systematically analyze the independent and combined effects of abnormal sleep duration and insufficient physical activity on the risk of cognitive impairment in older Chinese adults, to elucidate the regulatory mechanisms of physical activity in the sleep-cognition relationship, and to provide a robust scientific foundation for the development of multidimensional cognitive health intervention strategies.MethodsA total of 5,184 older adults (aged 60 years and above) were selected for analysis from the 2020 China Health and Retirement Longitudinal study (CHARLS) data. The Mini-Mental State Examination (MMSE) and the International Physical Activity Questionnaire-Short Form (IPAQ-SF) were utilized to assess cognitive function and physical activity levels, respectively. Multifactorial logistic regression models were employed to analyze the independent and joint effects of sleep duration and physical activity on cognitive impairment, as well as to investigate the moderating role of physical activity.ResultsBoth short sleep duration (less than 6 h per night, OR = 1.274, 95%CI: 1.099 ~ 1.477) and long sleep duration (more than 8 h per night, OR = 1.228, 95%CI: 1.044 ~ 1.445) significantly increased the risk of cognitive impairment. Additionally, low-physical activity levels (less than 600 MET-min/week, OR = 1.436, 95%CI: 1.091 ~ 1.890) were also associated with a heightened risk of cognitive impairment. The interaction between sleep duration and physical activity was significant; specifically, short sleep combined with low-physical activity (OR = 2.196, 95% CI: 1.385 ~ 3.484) and long sleep with low-physical activity (OR = 1.273, 95%CI: 1.078 ~ 1.503) significantly elevated the risk of cognitive impairment. The prevalence of cognitive impairment was significantly different (p < 0.01) between the group with suitable sleep and moderate-high physical activity (24.01%) and the other combination groups.ConclusionThe results of this study support the hypothesis that sleep duration and physical activity levels may collaboratively enhance cognitive health through various physiological mechanisms. Furthermore, the findings suggest that a combination of sleep and physical activity interventions could be effective in preventing cognitive decline in the older adults population. However, due to the inherent limitations of the cross-sectional design, the findings reflect only statistical associations rather than causal relationships between the variables. Future studies should employ prospective designs and objective measures to investigate the causal relationships and underlying mechanisms in greater depth.